Pedagogical strategies focused on special educational needs: results of a pilot test of an Integrating Project - Pherez Gómez, Gustavo Adolfo; Vargas Amézquita, Sonia Lucia; Melo Romero, Erika Yamila (Unaciencia, Revista de Estudios e Investigaciones, 2020)
This study aims to propose a didactic strategy that surpasses the conventional models of subject pedagogy, which favor the segmentation of knowledge and that do not necessarily respond to the needs of the context. To this end, the Integrating Project has been chosen, which intends to intertwine the specific knowledge of the subjects: Curricular Strategies for Special Populations, Elective Deepening V and Pedagogical Practice IV for Special Populations, in order to generate awareness and acquire didactic strategies for the intervention in populations with Special Educational Needs (SEE). This was originated from a research study with a descriptive qualitative approach, of action research type, in which executives, teachers and students of the VIII semester of the Preschool Bachelor of the Faculty of Education of the UNAC participated, and the survey and the structured interview were implemented as information gathering techniques. The results show that the educators will consider that the Integrative Project is an inclusive, adequate, novel and pertinent proposal regarding the reality and the needs that are presented in the environment, specifically for the Initial Education environment; facilitating the optimization, the potentialization of knowledge, time and work strategies in the classroom, both for teachers and for participating students. The students state that the strategies have been effective because they are very applicable, since the lessons learned can be applied to various contexts. Awareness allows different people to have a general knowledge about these disabilities. Sign language allows interaction with students in practice, and the Universal Design for Learning (UDL) is applicable in the classroom.
Keywords: Array; Array; Array